Cyclooxygenase-2 promotes tumor growth and suppresses tumor immunity - Liu, Bing (Cancer Cell Int, 2015)
Cyclooxygenase-2 (COX-2), an inducible form of the enzyme that catalyzes the first step in the synthesis of prostanoids, is associated with inflammatory diseases and carcinogenesis, which is suspected to promote angiogenesis and tissue invasion of tumors and resistance to apoptosis. Meanwhile, COX-2 contributes to immune evasion and resistance to cancer immunotherapy, which plays a crucial role in the innate and adaptive immune response. The activity of COX-2-PGE2-EP signal pathway can suppress Dendritic cells (DCs), natural killer (NK), T cells, type-1 immunity excluding type-2 immunity which promote tumor immune evasion. COX-2 and the prostaglandin cascade play important roles in the “inflammogenesis of cancer”. In addition, COX-inhibitors can inhibit tumor immune evasion. Therefore, we can exert the COX-inhibitors to facilitate the patients to benefit from addition of COX-inhibitors to standard cytotoxic therapy.